Assessment of Knowledge and Attitude of women towards Menopause (Journal of Hama University, 2020)
Menopause is a special event in a women’s life as it has a major impact on the quality of their lives, it also indicates the end of a women’s reproductive life. During most of the women suffer from annoying symptoms, and they may need to be treated, However their information and their attitudes towards the menopause and its accompanying problems are a major factor improving the quality of this stage of their lives and ease their jobs. The results showed that most of the women’s 67 % their level of information was moderate on the menopause ,symptoms and its complication, and that the highest percentage  59 % had a positive attitude towards the menopause and 39,5 % of them had a neutral attitude and a very few percent 1,5 % has a negative attitude towards it. The study recommended conducting educational courses for women in health centers about menopause in all its aspects, the need for specialized centers that provide care and advice for menopausal women, and conducting a broader and more comprehensive study at the country level to assess the information and attitude of Syrian women about menopause